Estimaltion of the Entamoeba histolytica imd Blastocystis Aomz.#z.s among Patients in Baghdad Teaching Hospital
Objective: To estinate infections agents of diarrhea and infection rate with intestinal parasites in Baghdad Teaching Hospital, and its relationship with factors influencing their spread. Methodology: A total of (1374) stool sample were collected from patients who attended to Baghdad Teaching Hospital with different ages and they were divided into (11) age groups from beginning of July 2007 till the end of June 2008, were taken notes about age, gender. These participants were examined by concentration method by using saturated salt solution and Iodine stain. Results: The results showed that the infection rate with E#famoeba AisfodyJj.ca was (21.5%), while the infection rate with B/cisfoc)/a/i.s faom;.#i.s was (19.2%). The results revealed that there was a significant difference between the infection rate for both parasites and the monthly variation. The highest infection for both parasites was in October and February months respectively, while the lowest infection was during April and October months respectively. There were significant differences between gender and infection with E#/amoeb Ai.s/a/yf!.ca, B/as/oeys/7.a Aomi.»z.5, females were more than males in infection with E»/c7moe6a Air/ofyfz.ca and vice versa for infection with B/asJoeysfz.£ Ao"I.w;s, males were more than females. Significant differences were noted in the percentage of infection in relation to patient age in both parasites. The highest infection rate with E#/omoeda %J.a/a/yfi.ca and B/a/ocys/is ¢omJ.#J.a in age group (35-less 40) year, (10-less 15) year respectively and the lowest infection in age group (5-lesslo) year and (I day-less 5) year respectively. Recommendations: This study showed high infection rate with E#/clmoez)4 Ai.sfofy/i.ca and B/a5/oc